Namūżaj Ta’allum al-Jidāl al-Arabi ala Asās Naẓariyyat at-Ta’allum al-Bināiyah (April & October, 2025)
Nowdays, an Arabic learning and teaching in Indonesia currently has experience various developments and renewals. One of these developments and renewals was the emergence of Arabic learning and teaching model in the style of Arabic debate based on constructivist learning theories. This study aims to applicate constructivist theories in learning arabic. This research was qualitative research with an applied research approach. The research sample was students of Hasyim Asy’ari University Jombang with the research instrument was the researcher himself. While the data analysis that used in this research was descriptive analysis. The results showed that constructivist theories can be applied to Arabic learning and teaching with an Arabic debate, concidering with the principle of constructivist theories that the learning was mostly done with social groups and the students construct their own knowledge, while educators only act as facilitators which help students to build their own knowledge through higher order thinking skills (HOTS) especially on the analysis process.